The Impact of Performance Quality on Strengthening Strategic Position: A Case Study of a Textile and Leather Factory in Baghdad (International Journal of Financial, Administrative and Economic Sciences, 2026)
From a strategic perspective, the concept of competitor quality is a decisive factor in strengthening an organization’s strategic position, as success is not merely about outperforming any competitor, but rather outperforming the strongest, high-quality competitors. This necessitates operational and financial efficiency and a competitive position that drives the adoption of more modern and flexible strategies. However, this requires the organization to maintain strategic vigilance, which helps identify environmental threats and risks while building stronger strategic social networks—factors that necessitate finding effective ways to address and manage them as effectively as possible. Its Contribution to Shaping the Practical Reality of Contemporary Strategic Management: Fostering Excellence and Innovation. The presence of strong competitors compels an organization to improve its operational, financial, and competitive performance. This pressure drives the adoption of more modern and flexible strategies, thereby strengthening its position. Activating Strategic Vigilance: Fierce competition requires effective strategic vigilance systems, which help monitor threats and environmental risks, thereby fostering the organization’s strategic renewal. Shaping Expectations and Building Networks: Confronting strong competitors helps refine the organization’s ability to accurately articulate its needs, and build stronger strategic social networks, ensuring a better market position. Enhancing Strategic Planning High-quality competition requires defining a clear vision and mission and conducting a thorough analysis of the internal and external environment, which improves performance quality. In short, a weak competitor offers an easy victory, but a strong (high-quality) competitor builds a strong organization, as the quality of competition necessitates raising the levels of planning and execution to ensure survival and strategic excellence. The factory under study— (textile and leather factory). Since the dawn of the knowledge era, this has been achieved through high employee performance and the application of international standards in competition. The research sample consisted of either a convenience sample (100) or a random sample (50) of employees in the production department of the factory under study.
Keywords: Performance; Quality; Competitiveness; Strategy